Development of negative ion source with combined discharge - Goretskii, V.P.; Dobrovolskiy, A.M. (Вопросы атомной науки и техники, 2015)
The results of investigation of emission productivity of negative particles source with combined discharge are presented. A cylindrical beam of negative hydrogen ions with density about 5 A/cm² on source emission aperture is obtained. The full beam current values are up to 200 mA for negative hydrogen ions and up to 1.5 A for electrons with high divergence after source. The source has simple design and produces stable discharge with low level of oscillation. Представлено результати досліджень емісійних особливостей імпульсного джерела негативно заряджених часток з комбінованим типом розряду. Отримано циліндричний пучок негативних іонів водню з густиною 5 А/см² на емісійній апертурі джерела. Загальний струм негативних іонів водню досягає 200 мА, а електронів – 1,5 А, але має значне розходження на виході з джерела. Джерело має просту конструкцію та стабільні характеристики розряду з низьким рівнем коливань. Представлены результаты исследований эмиссионных особенностей источника отрицательно заряженных частиц с комбинированным типом разряда. Получен циллиндрический пучок отрицательных ионов водорода с плотностью 5 А/см² на эмиссионной апертуре источника. Полный ток отрицательных ионов водорода достигает 200 мА, а электронов – 1,5 А, но имеет значительную расходимость на выходе источника. Источник имеет простую конструкцию и стабильные характеристики разряда с низким уровнем колебаний.